骨髄コンディショニング方法 (2025)
本開示は、対象をコンディショニングする方法及び／または造血細胞移植（ＨＣＴ）を必要とする対象の骨髄における細胞の集団を枯渇させる方法であって、対象における内因性造血幹細胞（ＨＳＣ）上の標的に結合する抗体を投与することを含む、方法に関する。好適な実施形態において、標的はＣＤ１１７（ｃ－ｋｉｔ）である。【選択図】なし The present disclosure relates to methods of conditioning a subject and/or depleting a population of cells in the bone marrow of a subject in need of a hematopoietic cell transplantation (HCT) comprising administering an antibody that binds to a target on a endogenous hematopoietic stem cell (HSC) in the subject. In a preferred embodiment, the target is CD 117 (c-kit).